Pengaruh Lingkungan Kerja dan Komitmen Organisasi Terhadap Kinerja Pegawai di Delapan Desa Se-Kecamatan Magepanda Kabupaten Sikka: (Studi Kasus pada Konsumen Kecamatan Magepanda Kabupaten Sikka) - Ronaldo Erbara Putra; Maria Silvana Mariabel Carcia; Margaretha Yulianti (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The background of this research was the underachievement of performance targets This study aimed to (1) describe employee performance, the work environment, and organizational commitenent, and (2) analyze the influence of the work environment and organizational commitment on employce performance, both partially and sirsultaneously The population in this study consisted of employees from eight villages in the Magepanda District of Sikka Regency, totaling 64 people. Due to the limited population, the research was conducted as a cemus or saturated sampling. Data were collected through questionnaires and were analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted through F-tests and T-tests. The descriptive analysis results indicated that the variables of employee performance, work environment, and organizational commitment were categorized as good. The T-test results showed that the work environment variable had a negative and insignificant effect on employee performance, while organizational commitment had a positive but insignificant effect on employee performance. The F-test results showed that, simultaneously, all independent variables had an insignificant effect on employee performance. The determination analysis results indicated that the two independent variables in this study explained only 0.2% of the variation in employ ce performance in the eight villages of Magepanda District, Sikka Regency